Transformasi Zero Waste Lifestyle: Pemberdayaan Bank Sampah Berkah di Desa Karanganyar Melalui Pelatihan Pembuatan Eco-Enzyme - Setyorini, Fitri Adi; Pujiyanto, M. Aris; Ratnaningsih, Hanim Rahayuani; Putri, Rizkia Anandhita; Ibrahim, Shabrina Khalisah (Abdimas Universal, 2025)
The empowerment of the Berkah Waste Bank Community in Karanganyar Village aims to transform a zero-waste lifestyle through eco-enzyme training. This community service project was motivated by the vital role of waste banks in reducing waste volume through the collection, sorting, and recycling of economically valuable waste. However, managing organic waste has been a challenge due to limited awareness and knowledge of sustainable organic waste management and inadequate infrastructure. The primary goal of this program is to enhance the capacity and independence of the Berkah Waste Bank Community in effectively managing organic waste. The methods implemented included socialization, training, technology application, mentoring, and program evaluation. The intended outcomes were increased productivity and independence of the community, improved quality of organic waste processing, and enhanced welfare of members through eco-enzyme technology adoption. Initial results showed that training and mentoring significantly increased participants' knowledge, skills, and productivity in waste processing, promoting the adoption of sustainable organic waste practices.